(untitled) (Brazilian Journal of Radiation Sciences, 2022)
Brazil is one of the world’s largest grain producers, and inadequate storage favors the appearance of pests. Among the most important insect species, the genus Sitophilus and Tribolium stand out. The constant use of chemical pesticides leads to the selection of resistant populations and the need to study different methods for integrated control. Considering these aspects, the present study aimed to evaluate the mortality of adult individuals of S. zeamais in brown rice and T. castaneum in wheat flour, collected on substrates sold in the retail trade in São Paulo/SP city, exposed to increasing doses of gamma radiation. The experiment was carried out at the Radiation Technology Center at the Institute for Energetic and Nuclear Research – IPEN/USP, the substrates with the specimens were irradiated with doses of 0 (control), 25, 50, 75, 100, and 200 Gy in a Cobalt-60 source, type Gammacell 220, at a dose rate of 0.903 kGy/hour. The experiment consisted of 4 replicates per treatment and each replicate 10 insects, in a total of 40 insects per treatment, and the statistical design was completely randomized. The dose of 75 Gy was sufficient to obtain 100% efficiency for S. zeamais, but the dose of 200 Gy did not reach satisfactory efficiency for controlling T. castaneum. Therefore, a dose of 400 Gy should be recommended for the control of these two insect species in their respective substrates.